Epidemiological Characteristics and Temporal Trends of Dengue Fever in the Mlati 2 Primary Health Care, Sleman, Indonesia, 2021–2024 - Retno Widyaningrum; Liena Sofiana; Rokhmayanti Rokhmayanti; Desi Nurfita; Ardyawati Wira Oktaviana (Epidemiology and Society Health Review (ESHR), 2026)
Background: Dengue is a mosquito-borne viral disease transmitted mainly by Aedes aegypti and Aedes albopictus. A rapid increase in cases may indicate a potential outbreak and requires timely surveillance. This study aimed to describe dengue cases by person, place, and time in the Mlati 2 Public Health Center area from 2021 to 2024 and identify potential outbreak patterns. Method: This quantitative descriptive study used secondary data from epidemiological investigation records at Mlati 2 PHC. “Dengue cases” included all cases classified as DF, DHF, DSS, and DD. A total of 82 cases recorded from 2021 to 2024 were included. Data were analyzed descriptively and presented by person, place, time, laboratory diagnosis, and House Larvae-Free Index. Results: Most cases occurred among adults aged 19–59 years, with more females than males. Sumberadi Village recorded the highest number of cases, followed by Tlogoadi and Tirtoadi. DHF was the most frequent classification, while cases in 2024 showed more varied diagnoses, including DF, DHF, DD, and DSS. The three-year minimum–maximum pattern showed that cases in February, March, April, May, and August 2024 exceeded the historical maximum from 2021 to 2023, indicating potential outbreak signals. The House Larvae-Free Index remained below the national standard of 95% during the study period. Conclusion: Dengue cases occurred annually in the Mlati 2 Public Health Center area, with a marked increase in 2024. Cases were mainly found among productive-age adults and concentrated in Sumberadi Village. The potential outbreak signals and low House Larvae-Free Index highlight the need to strengthen surveillance, timely reporting, epidemiological investigation, and community-based vector control.